Menjelajahi Macan Studio: Upcycling sebagai Solusi Berkelanjutan untuk Limbah Tekstil - Christine, Ezra Nathalie (Universitas Ciputra Surabaya, 2025)
This research aims to provide fashion business owners with insights into the role of upcycling practices in building a sustainable brand. Upcycling offers a way to transform second-hand materials into unique, high-quality products, which can help reduce textile waste and appeal to environmentally conscious consumers. This study uses qualitative research methods, including case studies, interviews, literature reviews, and observations. Macan Studio serves as a key example, producing around 30 upcycled pieces each month, with 70% of materials sourced from second-hand items. Despite challenges in educating consumers about the value of upcycled fashion, especially in markets where second-hand is often associated with low cost, Macan Studio leverages social media and word-of-mouth marketing to build its brand presence. Engaging studio tours encourage customers to share their experiences online, while satisfied clients often spread positive feedback, further amplifying brand reach. Upcycling is shown to be not only eco-friendly but also a viable business strategy in the fashion industry. Through creativity and innovation, businesses can contribute to a more sustainable future while meeting the demands of modern consumers.